Box-Behnken Design for Extraction Optimization Followed by High Performance Countercurrent Chromatography: Production of a Flavonoid-enriched Fraction from Achyrocline Satureioides - Pittol, Vanessa; Ortega, George González; Doneda, Eduarda; Bianchi, Sara Elis; Santos, Marí Castro; Koetz, Mariana; Henriques, Amélia Teresinha; Bassani, Valquíria Linck (Planta Medica, 2020)
The biological properties of Achyrocline satureioides have been mostly ascribed to its major flavonoids quercetin (QCT), luteolin (LUT), and 3-O-methylquercetin (3OMQ). The present study aimed to optimize the extraction by dynamic maceration of the major phenolic compounds in order to obtain in a subsequent step a flavonoid-enriched fraction (FEF) using high performance countercurrent chromatography (HPCCC). A 3-level Box-Behnken design (BBD) was applied to maximize the extraction of the substances, using the plant : solvent ratio (X1), extraction time (X2), and ethanol concentration (X3) as factors. One-step HPCCC semipreparative separation with a solvent system composed of hexane : ethyl acetate : methanol : water (0.9 : 0.9 : 0.8 : 1.0, v/v) was employed to obtain the FEF. The second-order polynomial model was able to fit the experimental data adequately. The linear and quadratic terms of X3 were the most significant factors that affected all the responses. The positive linear term of X3 indicated a substantial increase in extraction yield, while the negative quadratic term showed a nonlinear tendency. Linear terms of X1 suggested a tendency to solvent saturation, except for QCT. The terms of X2 did not affect the responses substantially. The HPCCC method was found to be efficient and rapid for separating the FEF with 71% (w/w) flavonoid content. Overall, the developed extraction procedure coupled with HPCCC proved to be efficient for obtaining an enriched fraction with a very high content of flavonoids from A. satureioides.
Keywords: Achyrocline satureioides; Asteraceae; Box-Behnken design; extraction optimization; flavonoid; high performance countercurrent chromatography